2021
DOI: 10.3390/genes12040580
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Genetic Mechanism of Non-Syndromic Congenital Cataracts. Mutation Screening in Spanish Families

Abstract: Our purpose was to identify mutations responsible for non-syndromic congenital cataracts through the implementation of next-generation sequencing (NGS) in our center. A sample of peripheral blood was obtained from probands and willing family members and genomic DNA was extracted from leukocytes. DNA was analyzed implementing a panel (OFTv2.1) including 39 known congenital cataracts disease genes. 62 probands from 51 families were recruited. Pathogenic or likely pathogenic variants were identified in 32 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…Three variants were identified in connexin genes GJA8 and GJA3 . A GJA8 p.(Gly22Ser) change, observed in family CRCH137, has been previously reported 25 27 28 and is one meiosis short of reclassification as likely pathogenic ( table 1 , figure 3A ). In family CTAS71, the novel p.(Lys131del) change ( table 1 , figure 3B ) is located centrally in the GJA8 protein’s cytoplasmic loop which is a less conserved protein region in general.…”
Section: Resultsmentioning
confidence: 75%
“…Three variants were identified in connexin genes GJA8 and GJA3 . A GJA8 p.(Gly22Ser) change, observed in family CRCH137, has been previously reported 25 27 28 and is one meiosis short of reclassification as likely pathogenic ( table 1 , figure 3A ). In family CTAS71, the novel p.(Lys131del) change ( table 1 , figure 3B ) is located centrally in the GJA8 protein’s cytoplasmic loop which is a less conserved protein region in general.…”
Section: Resultsmentioning
confidence: 75%
“…The 14th (arginine), 25th (proline), and 150th (arginine) codons were most frequently reported, which are marked in red in Figure 2C . A Spanish author had reported that a missense mutation in c. C232T (p. Ser78Pro) resulted in nuclear cataract ( Fernández-Alcalde et al, 2021 ). Our variant amino acid site (78) was the same as that reported by the Spanish author, but our variant resulted in serine-to-phenylalanine substitution.…”
Section: Resultsmentioning
confidence: 99%
“… Ex3/5 c.313T>G p.F105V AR Iraq Presenile, cortical, sutural ( 12 ) 5. Ex4/5 c.385C>T p.R129C AD Spain - ( 13 ) 6. Ex4/5 c.388C>T p.R130C AD UK/Czechia Nuclear pulverulent ( 3 ) 7.…”
Section: Discussionmentioning
confidence: 99%